Portable green energy mobile laptop charging station - Al-Talib, Ammar Abdulaziz Majeed; Tan, Rodney H.G.; Jie, Angaun; Noor Idayu, Mohd Tahir; Sarah ‘Atifah, Saruchi; Cik Suhana, Hassan; Amar Ridzuan, Abd Hamid (A Life Robotics Corporation Ltd, 2024)
Mobile phones and laptop computers require electrical power to recharge when the battery is down. As a result, it would be very useful if a portable charging station derived from renewable energy harvesting could be built, so that individuals could recharge their phones and laptops whenever needed. The objective of this project is to design and develop a green energy mobile and laptop charging station that uses wind and solar energy and evaluate the performance of the designed station under different working conditions. The efficiency of the power generated to charge the station is achieving 95.6% for solar charging, which is considered a high efficiency for a renewable energy charging station. Based on the analysis of the charging station results, it has been proven that it can provide sufficient power and is safe for use as a portable mobile laptop charging station.